Breast Cancer Resistance to Cyclin-Dependent Kinases 4/6 Inhibitors: Intricacy of the Molecular Mechanisms - Wang, Bin; Li, Rui; Wu, Shuai; Liu, Xin; Ren, Jianlin; Li, Jing; Bi, Kaixin; Wang, Yanhong; Jia, Hongyan (Frontiers in Oncology, 2021)
Breast cancer is a common malignant tumor in women，with an highest incidence and mortality among all of the female malignant tumors[1]. Notably, targeted therapy has achieved impressive success in the treatment of breast cancer. As one class of the anti-tumor targeted therapeutics, Cyclin-Dependent Kinases 4/6 （CDK4/6 ）inhibitors have shown good clinical activity in treating breast cancer[2]. Nevertheless, despite the promising clinical outcomes, intrinsic or acquired resistance to CDK4/6 inhibitors has limited the benefits of this novel target therapy. In the present review, we provide an overview of the currently known molecular mechanisms of resistance to CDK4/6 inhibitors, and discuss the potential strategies to overcoming drug resistance improving the outcomes for breast cancer patients treated with CDK4/6 inhibitors.